THE DIAGNOSTIC COMPONENT OF FUNDAMENTALIZATION OF THE BASIC MATHEMATICAL PREPARATION OF THE FUTURE SPECIALISTS OF A TECHNICAL PROFILE AT HIGHER EDUCATIONAL ESTABLISHMENTS - Tetyana Yarkho (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The process of fundamentalization of the mathematical preparation of the future specialists of a technical profile at higher educational establishments, complying with a new model of education based on the principles of a competence-based approach, requires modernization of the existing systems and technologies of education quality control. The paper presents the ideology of the diagnostic component of fundamentalization of the basic mathematical preparation in the area of controlling the formation of the mathematical competence of the future specialists of a technical profile under the conditions of multi-step higher education. The consistent realization of a complex of the successive forms of control has been suggested: the propaedeutic, thematic, periodical, final and residual ones. The content bulk and the technology of implementing the indicated forms of control presuppose keeping tabs on measures of fundamentalization of mathematical preparation of the future specialists of a technical profile at higher educational establishments.